Characterization of the oil from the abdomen part of smoked catfish (Pangasius hypophthalmus) processing by-product - Dewi Fortuna Ayu; Andarini Diharmi; Akhyar Ali (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2019)
Smoke catfish (Pangasius hypophthalmus) processing place produces waste in the form of fish entrails. Abdominal fat is the main component of fish entrails and is a source of fish oil. This study was aimed to determine the physicochemical characteristics and composition the catfish abdominal fat. The oil was extracted by rendering the abdominal fat at 70°C for 5 h followed up by purification through bentonite and active charcoal. Crude catfish oil was observed to be semi-solid in texture, yellow and fishy. The purification improved the characteristics of the fish oil. The purified fish oil was white and less fishy. Furthermore, the purification step reduced the free fatty acid content, the acid number and peroxide value up to 11; 4 and 3 fold, respectively. Palmitic, stearic and myristic acid dominated saturated fatty acid group, representing 26.22; 5.06 and 2.85% of the total fat, respectively. Meanwhile, oleic and linoleic represented 40.14 and 19.97 of the total fat, respectively and were the dominant fatty acid of the unsaturated fatty acid group.